BH, CH, and BC Bond Activation: The Role of Two Adjacent Agostic Interactions1. Issue 29 (2nd July 2014) - Cassen, Audrey; Gloaguen, Yann; Vendier, Laure; Duhayon, Carine; Poblador‐Bahamonde, Amalia; Raynaud, Christophe; Clot, Eric; Alcaraz, Gilles; Sabo‐Etienne, Sylviane
Abstract Tuning the nature of the linker in a L∼BHR phosphinoborane compound led to the isolation of a ruthenium complex stabilized by two adjacent, δ‐CH and ε‐Bsp2H, agostic interactions. Such a unique coordination mode stabilizes a 14‐electron "RuH2P2" fragment through connected σ‐bonds of different polarity, and affords selective BH, CH, and BC bond activation as illustrated by reactivity studies with H2 and boranes.